If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y + -5(3y + -13) = 0 Reorder the terms: 9y + -5(-13 + 3y) = 0 9y + (-13 * -5 + 3y * -5) = 0 9y + (65 + -15y) = 0 Reorder the terms: 65 + 9y + -15y = 0 Combine like terms: 9y + -15y = -6y 65 + -6y = 0 Solving 65 + -6y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-65' to each side of the equation. 65 + -65 + -6y = 0 + -65 Combine like terms: 65 + -65 = 0 0 + -6y = 0 + -65 -6y = 0 + -65 Combine like terms: 0 + -65 = -65 -6y = -65 Divide each side by '-6'. y = 10.83333333 Simplifying y = 10.83333333
| 22+d=31 | | f+5=9 | | 2y-7/(3)-6y-9/(14)=3y-5/(21) | | 2x+2(x+5)=34 | | -7(r*r+2)+3r*r= | | 4+25x=20x+5 | | (2y-7/3)-(6y-9/14)=(3y-5/21) | | 3/7y-9=-6 | | 39+n=75 | | -3(2y+2)-4=-4(y+6)+2y | | 4x-10-12+18x=6 | | x+35=79 | | 2y-7/3-6y-9/14=3y-5/21 | | 61+y=80 | | 6e^2x=9e^4x | | -18=9x-(4x-5) | | x^2-85x-1500=0 | | y=-4/9x-0.8 | | 4cos^2(x)-4cosx+1=0 | | -16+4x=-32+18x | | -5(3n-5)=30 | | 4a-6b=0 | | 4cos^2(x)-4cos(x)+1=0 | | x^2=5(x-3) | | -10=15x-(9x-1) | | s+11=42 | | 3r=59 | | 37-2x=13-8x | | 30=8+x | | -5x+48=8 | | lg(25x)=0 | | 8x-(3+6x)=36 |